Biopsychosocial obstetrics and gynaecology – a perspective from Australia. (2nd January 2016) - Rowe, Heather
Abstract: Prior to and throughout the twentieth century, biomedical understandings of health predominated. Australian obstetrician and gynaecologist, Professor Derek Llewellyn-Jones responded to frustrations with the limitations of this narrow approach from both within and beyond the medical profession. His pioneering research, education and writings re-conceptualised the discipline as encompassing the social and psychological contexts and profoundly influenced women's own understanding of their health and the practice of obstetrics and gynaecology. The biopsychosocial model has replaced biological determinism and is now pervasive in education and clinical practice in many parts of the world. Widespread acceptance of the model has until now been associated with under-recognition of the importance of biology. Recent findings from epigenetics and neuroscience are enabling integration of body, mind and society and enhanced understanding and practice of psychosomatic obstetrics and gynaecology.